Market and non-market monetary policy tools in a calibrated DSGE model for mainland China - Qianying Chen; Michael Funke; Michael Paetz (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
Monetary policy in mainland China differs from conventional central banking in several respects. The central bank regulates retail lending and deposit rates, influences the credit supply via window guidance, and, in recent years has even used the required reserve ratio as a tool for fine-tuning monetary policy. This paper develops a New Keynesian DSGE model to captures China s unconventional monetary policy toolkit. We find that credit quotas are important as the interest-rate corridor distorts the efficient reactions of the economy. Moreover, for China s central bankers the choice of a particular monetary policy tool or a the appropriate combination of instruments depends on the source of the shock.
URN:NBN:fi:bof-201408072108
Keywords: 330